Factors Influencing the Persistence of Salmonella Infantis in Broiler Litter During Composting and Stabilization Processes and Following Soil Incorporation - Avidov, Ran; Varma, Vempalli Sudharsan; Saadi, Ibrahim; Hanan, Aviva; Lublin, Avishai; Saldinger, Shlomo Sela; Chen, Yona; Laor, Yael (Frontiers in Sustainable Food Systems, 2021)
Broiler litter (BL), a by-product of broiler meat production, is frequently contaminated with Salmonella and other zoonotic pathogens. To ensure the safety of crop production chains and limit pathogen spread in the environment, a pre-treatment is desired before further agricultural utilization. The objective of this study was to characterize the effect of physico-chemical properties on Salmonella persistence in BL during composting and stabilization and following soil incorporation, toward optimization of the inactivation process. Thirty-six combinations of temperature (30, 40, 50, and 60°C), water content (40, 55, and 70%; w/w), and initial pH (6, 7, and 8.5) were employed in static lab vessels to study the persistence of Salmonella enterica serovar Infantis (S. Infantis; a multidrug-resistant strain) during incubation of artificially-inoculated BL. The effect of aeration was investigated in a composting simulator, with controlled heating and flow conditions. Temperature was found to be the main factor significantly influencing Salmonella decay rates, while water content and initial pH had a secondary level of influence with significant effects mainly at 30 and 40°C. Controlled simulations showed faster decay of Salmonella under anaerobic conditions at mesophilic temperatures (<45°C) and no effect of NH3 emissions. Re-wetting the BL at mesophilic temperatures resulted in Salmonella burst, and led to a higher tolerance of the pathogen at increased temperatures. Based on the decay rates measured under all temperature, water content, and pH conditions, it was estimated that the time required to achieve a 7 log10 reduction in Salmonella concentration, ranges between 13.7–27.2, 6.5–15.6, 1.2–4.7, and 1.3–1.5 days for 30, 40, 50, and 60°C, respectively. Inactivation of BL indigenous microbial population by autoclaving or addition of antibiotics to which the S. Infantis is resistant, resulted in augmentation of Salmonella multiplication. This suggests the presence of microbial antagonists in the BL, which inhibit the growth of the pathogen. Finally, Salmonella persisted over 90 days at 30°C in a Vertisol soil amended with inoculated BL, presumably due to reduced antagonistic activity compared to the BL alone. These findings are valuable for risk assessments and the formulation of guidelines for safe utilization of BL in agriculture.